Risk factors for refractory Mycoplasma pneumoniae in Chinese children: a meta-analysis - Chun Chen; Shan Chen; Chuanzhong Yang; Xiaolan Zhang; Luohui Liu; Yuejuan Wang; Min Cao (Frontiers in Pediatrics)
BackgroundWith the increase of the incidence rate of Mycoplasma pneumoniae in children and the widespread use of azithromycin, the number of cases of refractory M. pneumoniae increased accordingly. M. pneumoniae infection was generally considered a self-limiting disease. However, under certain special circumstances, it was highly likely to develop into a refractory disease. This study conducted a meta-analysis of early risk factors for refractory Mycoplasma pneumoniae pneumonia (RMPP), which was helpful for the early clinical diagnosis of RMPP and the reduction of sequelae.MethodsThis systematic search was conducted in Web of Science, Embase, PubMed, Cochrane Library, CNKI, Wangfang, Sinomed and Cqvip, and the date was set until August 20, 2024. After two researchers independently screened the literature, extracted data, and assessed the risk of bias in the included studies, a meta-analysis was conducted using STATA 17.0 and RevMan 5.4 software.ResultsTwenty-eight studies including 6374 patients were included in this analysis, and the results showed that the age [MD (95% CI): 0.62 (0.21, 1.03), P = 0.003], LDH [MD (95% CI): 161.57 (128.22, 194.91), P < 0.001], neutrophils (%) [MD (95% CI): 9.27 (3.45, 15.09), P = 0.002], IL-6 [MD (95% CI): 23.07 (20.90, 25.24), P = 0.04], ESR [MD (95% CI): 10.93 (7.75, 14.11), P < 0.001], AST [MD (95% CI): 16.11 (8.21, 24.01), P < 0.001], ALT [MD (95% CI): 23.69 (9.60, 37.77), P = 0.001], CRP [MD (95% CI): 23.72 (18.41, 29.03), P < 0.001], and WBC [MD (95% CI): 1.07 (0.28, 1.86), P = 0.008] were higher in the RMPP group than in the NRMPP group. Combined pleural effusion (OR = 7.59, 95% CI: 4.19–13.75, P < 0.001) and lung consolidation (OR = 10.61, 95% CI: 4.13–27.26, P < 0.001) were identified as risk factors for RMPP. However, no significant association was found between gender and the incidence of RMPP (OR = 0.91, 95% CI: 0.80–1.02, P = 0.10). The analysis of publication bias indicated that 3 of the 11 factors analyzed [LDH, neutrophils (%), and lung consolidation] showed significant publication bias (P < 0.05).ConclusionOur study further confirmed that elevated inflammatory markers such as CRP, LDH, neutrophils (%), IL-6, ESR, lung consolidation, combined pleural effusion were risk factors for RMPP. For the first time, WBC, ALT, and AST were identified as risk factors for the occurrence of RMPP in children. Additionally, demographic information such as age and gender was also examined in relation to RMPP in children.